Perancangan E-Commerce Pada Fakultas Teknologi Informasi Universitas Atma Jaya Makassar Sebagai Media Praktek Matakuliah Technopreneur - Arnold Nasir; Rizky Nugraha Amaia (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2019)
The main objective of this thesis is to develop e-commerce services on FTI-UAJM as a means by which students become entrepreneurs. The study was conducted using a waterfall methodology, consisting of a number of stages performed systematically. Through this research, it is known that the system can assist the academic community in marketing their work and also the practice means for students who take the technopreneur course, where the system is integrated directly with the technopreneur course so that it can be monitored directly and evaluated by the lecturer.